Measurement and decomposition of education-related inequality in exclusive breastfeeding practice among Ethiopian mothers: applying Wagstaff decomposition analysis - Dessie, Anteneh Mengist; Zemene, Melkamu Aderajew; Gebeyehu, Asaye Alamneh; Anley, Denekew Tenaw; Anteneh, Rahel Mulatie; Moges, Natnael; Chanie, Ermias Sisay; Tsega, Sintayehu Simie; Belete, Melaku Ashagrie; Alemayehu, Ermiyas; Kebede, Natnael (Frontiers in Public Health, 2024)
BackgroundHuman breast milk, a naturally balanced source of infant nutrition, promotes optimal growth and health when exclusively fed for 6 months. Exclusive breastfeeding reduces common childhood infections, provides protection against some chronic illnesses, and contributes to achieving several Sustainable Development Goals. Despite its benefits, only 58% of Ethiopian women practice it, and the associated education-related inequality is not well documented. Thus, this study aims to quantify and decompose the education-related inequality in exclusive breastfeeding practice among Ethiopian mothers.MethodsA total of 1,504 weighted samples were studied using a Performance Monitoring for Action Ethiopia longitudinal panel survey dataset (2021–2023). Wagstaff normalized concentration index and its concentration curve were used to assess education-related inequality in exclusive breastfeeding practice. Wagstaff decomposition analysis was performed to decompose the concentration index and identify factors contributing to the observed education-related inequality. Significance was declared at p-value <0.05.ResultsThe overall prevalence of exclusive breastfeeding among Ethiopian women was 57.29% (95% CI: 54.79, 59.80%), with a greater concentration found among women with lower levels of education. This indicates an inequality that favors less educated women (pro-less educated inequality), as demonstrated by the Wagstaff normalized concentration index of −0.058 (95% CI: −0.113, −0.002). Factors that made a significant contribution to the observed education-related inequality in exclusive breastfeeding practice were residence (18.80%), region (29.31%), place of birth (−7.38%), and the wantedness status of the indexed pregnancy (82.58%). The indexed pregnancy’s wantedness was made a more elastic (elasticity = 0.282) contribution.ConclusionThe study identified a small yet significant education-related inequality in exclusive breastfeeding, favoring less educated women. Hence, emphasis should be placed not only on educating women but also on healthy habits that they can leave behind when they learn. Residence, region, place of birth, and indexed pregnancy’s wantedness significantly contributed to the observed education-related inequality. The elasticity value for each factor suggests that policy changes addressing these factors could readily reduce the observed inequality.